Approximate controllability of the nonlinear third-order dispersion equation - Sakthivel, R.; Mahmudov, N. I.; Ren, Yong (Elsevier Science Inc, 2011)
In this paper, we consider the approximate controllability of nonlinear third-order dispersion equation of the form partial derivative w/partial derivative t (x, t) + partial derivative(3)w/partial derivative x(3) (x, t) = (Gu)(x, t) + f (t, w(x, t)) on the interval 0 <= x <= 2 pi, t >= 0 with initial and periodic boundary conditions w(x, 0) = 0, partial derivative(k)w/partial derivative x(k) (0, t) = partial derivative(k)w/partial derivative x(k) (2 pi, t), k = 0, 1, 2. We study the approximate controllability for nonlinear dispersion system under the assumption that the corresponding linear control system is approximately controllable. The solutions are given by a variation of constants formula which allows us to study the approximate controllability for nonlinear dispersion systems. Based on the semigroup theory and fixed point approach, sufficient conditions are formulated and proved. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: Approximate controllability; Semigroup theory; Nonlinear dispersion system; Korteweg-de Vries equation; Fixed point theorem